The Fate of Glyphosate in Soil and Water: A Review - Suwardji Suwardji; ‪I Made Sudantha (Postgraduate, University of Mataram, 2021)
The fate of glyphosate in soil and water is dependent on the properties of glyphosate and its envoronement. Behaviour of glyphosate in soil, sediment and water is strongly influenced the way by which it can be adsorbed by soils, sediments, and suspended material in water. The role of soil organic matter, clay mineral, and amorphous minerals on the adsorption of glyphosate depends primarily on the nature and properties of the soil itself and the properties of glyphosate. Environmental factors have some influence on sorption and degradation of glyphosate. Glyphosate is rapidly inactivated in soil, is in part due to adsorption. Some soil properties have been identified strongly influence adsorption of glyphosate, such as clay minerals, composition of cations in exchangeable site of clay and organic matter, unoccupied phosphate adsorption site, degree of humification, and soil pH. Adsorption limits the availability of glyposate for microbial degradation. The sorbed glyphosate is not directly available to microorganisms in soil. Evidence also suggests that not only a strongly sorbed compound such as paraquat but also weakly sorbed compounds such as flumetsulam and picloram can persist for long periods when they are sorbed by soil constituents. This suggests that the interaction between sorption and biodegradation should be considered in predicting the fate of pesticides in soils and sediments.